Ultra-Short Pulse HiPIMS: A Strategy to Suppress Arcing during Reactive Deposition of SiO2 Thin Films with Enhanced Mechanical and Optical Properties - Tiron, Vasile; Velicu, Ioana Laura; Matei, Teodora; Cristea, Daniel; Cunha, Luis; Stoian, George (MDPI AG, 2020)
In this contribution, based on the detailed understanding of the processes’ characteristics during reactive high-power impulse magnetron sputtering (HiPIMS), we demonstrated the deposition of silicon oxide (SiO2) thin films with improved optical and mechanical performances. A strategy for stabilizing the arc-free HiPIMS of Si target in the presence of oxygen was investigated. Arcing was suppressed by suitable pulse configurations, ensuring good process stability without using any feedback control system. It was found that arcing can be significantly alleviated when ultra-short HiPIMS pulses are applied on the target. The optical and mechanical properties of SiO2 coatings deposited at various pulsing configurations were analyzed. The coatings prepared by ultra-short pulse HiPIMS exhibited better optical and mechanical performance compared to the coatings prepared by long pulse HiPIMS. The optimized SiO2 coatings on quartz substrates exhibited an average transmittance of 98.5% in the 190–1100-nm wavelength range, hardness of 9.27 GPa, hardness/Young’s modulus ratio of 0.138, and critical adhesion load of 14.8 N. The optical and mechanical properties are correlated with the film morphology, which is inherently related to energetic conditions and process stability during film growth.
Keywords: reactive HiPIMS; silicon oxide; arcing; mechanical properties